Change of the levels of trace elements and heavy metals in threatened abortion. Issue 7 (July 2019) - Turan, Kasim; Arslan, Ayşe; Uçkan, Kazim; Demir, Halit; Demir, Canan
Abstract : Backround: This study aimed to investigate the impact of changes in the serum levels of trace elements and heavy metals in threatened abortion, which is a common complication in early pregnancy. Earlier studies have shown that changes in the serum levels of some trace elements and increased serum concentrations of heavy metals are associated with spontaneous abortion; however, this relationship has not been fully clarified. Methods: The patient group consisted of 45 pregnant women diagnosed with threatened abortion. There were 40 healthy nonpregnant women in the control group. Blood samples were obtained from the patients and the healthy controls, and the concentrations of serum trace elements and heavy metals were measured using atomic absorption spectrophotometry. Results: Statistically significant decreases were found in the serum zinc (Zn), iron (Fe), magnesium (Mg) and manganese (Mn) levels, and significant increases were found in the serum copper (Cu), cadmium (Cd) and lead (Pb) levels in cases of threatened abortion in comparison to the controls ( p < 0.001). However, there was no difference between the groups in terms of the serum cobalt (Co) levels ( p > 0.001). Conclusion: Changes in the balance of some essential trace elements (especially decreases in Fe and Zn) and elevated concentrations of some toxic heavy metals in the blood may be important diagnostic and prognostic parameters for threatened abortion